Sculptured tombs of Hellas - Gardner, Percy, 1846-1937 (Salt Lake City, UT : Project Gutenberg, 2022)
"Sculptured Tombs of Hellas" by Percy Gardner is a scholarly exploration of ancient Greek burial customs, written in the late 19th century. This work delves into the significance of sepulchral monuments, examining their artistic and cultural implications within the ancient Greek psyche and societal practices concerning death. Gardner addresses not only the structures themselves but also the rituals surrounding mourning and the offerings made to the dead. The opening of the text introduces the profound connection between burial customs and the cultural consciousness of ancient Greece, emphasizing the importance of funerary practices in relation to general societal beliefs about life and death. Gardner articulates that the public expressions found in literature and art often reflect highbrow sentiments that differ from the common people's perspectives on mortality. He outlines the structure of the book, which will address Greek burial practices, beliefs about the afterlife, and a focused study of the tombs and monuments that characterize significant regions such as Athens and Asia Minor, providing a robust context for understanding these sculptural tombs. (This is an automatically generated summary.)
Release date is 2022-12-09
Chuck Greif, deaurider and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Sculpture, Greek; Sepulchral monuments -- Greece; Funeral rites and ceremonies -- Greece